2022
DOI: 10.1111/ics.12784
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional activity of bakuchiol against cellular mechanisms of facial ageing ‐ Experimental evidence for a holistic treatment approach

Abstract: Objective: Skin ageing is a multifactorial process involving formation of reactive oxygen species, consecutive inflammation with reduced epidermal and dermal cell viability and resulting damage to the extracellular matrix. Effective dermocosmetic treatment modalities should ideally address these hallmarks in a holistic approach.Here, we determined the corresponding activity profile of bakuchiol, a plant-derived meroterpene, in an array of in vitro, ex vivo and in vivo studies and compared it to retinol, curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…The antioxidant properties of bakuchiol were outlined as an important mechanism against photoaging. Thus, its involvement in several antioxidant processes (e.g., oxygen radicals scavenging, inhibition of lipid peroxidation, activation of nuclear factor erythroid 2-related factor 2, a transcription factor involved in the cell resistance to oxidative stress) [ 64 , 65 , 66 ] support bakuchiol’s efficacy in topical skincare treatments against photoaging, as already shown by some clinical investigations [ 35 , 62 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The antioxidant properties of bakuchiol were outlined as an important mechanism against photoaging. Thus, its involvement in several antioxidant processes (e.g., oxygen radicals scavenging, inhibition of lipid peroxidation, activation of nuclear factor erythroid 2-related factor 2, a transcription factor involved in the cell resistance to oxidative stress) [ 64 , 65 , 66 ] support bakuchiol’s efficacy in topical skincare treatments against photoaging, as already shown by some clinical investigations [ 35 , 62 ].…”
Section: Discussionmentioning
confidence: 83%
“…Bakuchiol has already been highlighted as a quenching agent in several in vitro studies. Blumke et al showed that at a concentration of 100 µM, bakuchiol scavenged DPPH radicals to a greater extent than retinol [ 62 ]. At a similar concentration, the meroterpene exhibited 84.6% ABTS radical scavenging activity, a value comparable with that of the positive control resveratrol [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…This revealed that protocatechuic acid has the effect of skin anti-aging. Nature-Based bakuchiol: Natural bakuchiol has a strong antioxidant activity, which can significantly reduce the levels of PGE2 and MIF [ 63 ]. Female subjects (n = 60) with sensitive skin (e.g., eczema, blackheads, and cosmetic intolerance) were selected and they applied cosmetics containing natural bakuchiol according to the needs of the face for 4 weeks.…”
Section: Research On Skin Anti-aging Compoundsmentioning
confidence: 99%
“…Among the many active compounds found in plants, there are terpenoids, which include bakuchiol [1][2][3]-phenol) is partly phenolic and partly terpene, so it is a meroterpene that combines those two structural elements in a single molecule. Bakuchiol has many beneficial properties for living organisms such as anti-aging, anti-pigmentation, anti-acne, anti-cancer, hepatoprotective, cardioprotective, hypoglycemic, hypolipemic, and antidepressant, antioxidant, anti-inflammatory, antiobesity, and antimicrobial activities, moreover it shows the effect of reducing postmenopausal bone loss [4][5][6][7][8][9] . Mainly due to the antioxidant, antimicrobial, emulsifying, and skin-improving properties of bakuchiol, it is widely used in cosmetology and dermatology 1,7,10,11 .…”
mentioning
confidence: 99%